Trigger factors of comorbid allergic bronchial asthma formation - E. V. Nadey; V. I. Sovalkin; G. I. Nechaeva; V. V. Goltyapin; E. N. Loginova (Лечащий Врач)
A study was carried out with the participation of patients with allergic asthma, comorbid with allergic rhinitis and atopic dermatitis, with the aim of increasing the effectiveness of treatment with polyvalent sensitization by the administration of allergenspecific immunotherapy.